CLINICAL AND EPIDEMIOLOGICAL ANALYSIS OF SUICIDE ATTEMPTS IN CHILDREN ASSISTED BY A POISON CONTROL CENTER - Rafaele Maria Tirolla; Edmarlon Girotto; Camilo Molino Guidoni
ABSTRACT Objective: To assess suicide attempts in children seeking care at a Poison Control Center. Methods: Cross-sectional study with children (<12 years old) that attempted suicide and were cared at the Poison Control Center in Londrina, Paraná, Southern Brazil, from April 1985 to December 2018. Results: We identified 59 children, most of them females (74.6%), who used only one product (77.9%). Among the products involved, medications were the most important ones (88.1%). Neurological/psychiatric/muscular manifestations (61.0%) were the main symptoms presented. The main reason identified for the suicide attempt was conflicts with family and/or friends (27.1%). Suicide attempts were more frequent in 2001-2003 and 2016-2018. Conclusions: Suicide attempts occurred mainly in female children with a single agent (mainly medications), and the main reason was family conflicts..